2013
DOI: 10.1039/c2nr32156d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copper nanoparticles toxicity based on a stress-responsive bacterial biosensor array

Abstract: The rapid development in nanoparticle production and application during the past decade requires an easy, rapid, and predictive screening method for nanoparticles toxicity assay. In this study, the toxicological effects and the source of toxicity of copper nanoparticles (CuNPs) are investigated based on a stress-responsive bacterial biosensor array. According to the responses of the biosensing strains, it is found that CuNPs induce not only oxidative stress in E. coli, but also protein damage, DNA damage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Exposure to Cu NPs resulted in oxidative stress (measured by biotic reactive oxygen species (ROS) generation) for E. coli and L. brevis, but there was no effect from CuCl 2 , CuSO 4 , μCu or μCuO at the concentrations studied ([Cu] up to 250 mg/L) (Kaweeteerawat et al, 2015). These results are in line with previous work indicating that exposure to Cu NPs caused cellular oxidative stress in bacterial cells (Li et al, 2013), yeast cells (Kasemets et al, 2013), and mammalian cells (Liu et al, 2014). Exposure to ionic and nano-and micro-scale Cu particles resulted in DNA damage (using an in-vitro plasmid assay), but while nCu and μCu induced complete degradation of plasmid DNA, both n-Cu(OH) 2 converted the supercoiled plasmid to open circular (single-strand breaks) and linearized plasmid (double-strand breaks) (Kaweeteerawat et al, 2015).…”
Section: High Throughput/content Screening Studiessupporting
confidence: 82%
“…Exposure to Cu NPs resulted in oxidative stress (measured by biotic reactive oxygen species (ROS) generation) for E. coli and L. brevis, but there was no effect from CuCl 2 , CuSO 4 , μCu or μCuO at the concentrations studied ([Cu] up to 250 mg/L) (Kaweeteerawat et al, 2015). These results are in line with previous work indicating that exposure to Cu NPs caused cellular oxidative stress in bacterial cells (Li et al, 2013), yeast cells (Kasemets et al, 2013), and mammalian cells (Liu et al, 2014). Exposure to ionic and nano-and micro-scale Cu particles resulted in DNA damage (using an in-vitro plasmid assay), but while nCu and μCu induced complete degradation of plasmid DNA, both n-Cu(OH) 2 converted the supercoiled plasmid to open circular (single-strand breaks) and linearized plasmid (double-strand breaks) (Kaweeteerawat et al, 2015).…”
Section: High Throughput/content Screening Studiessupporting
confidence: 82%
“…At concentrations of 40-60 mg/ml, it is toxic to various organisms such as algae, bacteria, crustaceans, and fish [36]. The type and application mode of these compounds are important, as the global production of Ag and Cu in the form of NPs is estimated at more than 500 tons per year [37], and their industrial and agricultural use is constantly increasing [38].…”
Section: Characteristics Of Nanosilver and Nanocoppermentioning
confidence: 99%
“…For instance, Chen et al (2006) found that CuNPs could induce more severely pathological injuries to the kidney, liver, and spleen of mice compared to copper at micrometer size. On the other hand, a few studies have shown that copper ions could induce protein damage, membrane damage, slight DNA damage, and cell death (Li et al 2013). Therefore, it is essential to determine the changes in physicochemical properties (e.g., size, dissolution, and aggregation) of NPs during toxicological exposure to correctly interpret the doseresponse relationships and to avoid inaccurate dose estimation and the misinterpretation of toxicity results.…”
Section: Introductionmentioning
confidence: 99%